2022
DOI: 10.1101/2022.09.30.510372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Helicase” Activity Promoted Through Dynamic Interactions Between a ssDNA Translocase and a Diffusing SSB Protein

Abstract: Replication protein A (RPA) is a eukaryotic single stranded (ss) DNA binding (SSB) protein that is essential for all aspects of genome maintenance. RPA binds ssDNA with high affinity but can also diffuse along ssDNA. By itself, RPA is capable of transiently disrupting short regions of duplex DNA by diffusing from a ssDNA that flanks the duplex DNA. Using single molecule total internal reflection fluorescence and optical trapping combined with fluorescence approaches we show that S. cerevisiae Pif1 can use its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…In the absence of force, DBDs of RPA can bind distant sites at the same time and effectively stabilize the condensed DNA (65). Recent study on human RPA did not observe a significant influence of force on its diffusion (53). Our study on yeast RPA showed a clear force dependence on the diffusion of the protein both in experiment and simulations.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…In the absence of force, DBDs of RPA can bind distant sites at the same time and effectively stabilize the condensed DNA (65). Recent study on human RPA did not observe a significant influence of force on its diffusion (53). Our study on yeast RPA showed a clear force dependence on the diffusion of the protein both in experiment and simulations.…”
Section: Discussionsupporting
confidence: 40%
“…Although the effect of DNA tension on SSB diffusion on DNA has been studied previously (51), diffusive property of yeast RPA on ssDNA longer than 120 oligonucleotides length, or under mechanical tension, has not been reported yet. A recent study by Mersch et al have investigated diffusion of human RPA (hRPA) on 20 kbp long ssDNA and reported that the hRPA diffusion does not depend significantly on tension or salt concentration (53).…”
Section: Introductionmentioning
confidence: 99%